Graphite tattoo / Blue nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
The graphite tattoo is not exceptional in children who get it by voluntarily or inadvertently pricking themselves with a drawing pencil. Both clinically and dermoscopically the color of the tattoo can simulate a blue nevus.